Penyuluhan Gizi Seimbang pada Piring Saji untuk Bayi Dibawah Lima Tahun (Balita) agar Tumbuh dan Berkembang dengan Optimal - Dwi Nur Siti Marchamah; Saidatur Rohmah; Novita Sari (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
Nutritional intake is very important for optimal growth and health in the future. Factors that directly affect children's nutritional health problems, namely children not getting enough balanced nutritious food. Nutritional problems in toddlers can be avoided if the mother has sufficient knowledge about how to feed and manage toddler food properly, one of which is by getting health education. The purpose of this community service is to increase the understanding of PKK Jimus Village mothers to be able to apply balanced nutrition on serving plates for toddlers. The community service method is carried out by counseling, discussion, and mentoring. As for the results of the service, it was found that counseling and mentoring accompanied by discussions with PKK Jimus Village mothers had a positive impact on the understanding and application of balanced nutrition on serving plates for toddlers.